Matière Troyenne et exégèse dantesque - Punzi, Arianna (Troianalexandrina, 2018)
Abstract This paper studies the presence of the Trojan matter in the medieval exegesis of Dante Alighieri's Commedia. The result is a rather complex tradition which, beyond classical sources, was also enriched by the vernacular tradition, attesting the exceptional omnipresence of this matter in the Italian peninsule in the Middle Ages.